Regulation of an lncRNA irf8 by the Ikzf1/Myb complex drives neutrophil development - Yuepeng He; Yang Li; Yibo Shao; Xue Huang; Jiangyong He; Shengnan Liu; Yalan Xiao; Zhigang Li; Yu Hou; Lingfei Luo; Fangying Zhao; Li Li (Proceedings of the National Academy of Sciences, 2025)
As critical executors of the immune system, neutrophils provide an immediate inflammatory response for the clearance of debris and microbes, which is essential for the protection of health. Developmentally, neutrophils and macrophages share common progenitors, whose fate is tightly controlled by transcriptional programs. Dysregulation of these programs causes severe hematological disorders, including neutropenia, neutrophilia, leukemia, and inflammatory disorders. However, the mechanisms underlying the generation of neutrophils through these programs are poorly understood. Here, we revealed that Ikzf1 and Myb were enriched in neutrophils. Overactivation of Ikzf1 promoted neutrophil generation while suppressing macrophage emergence. Conversely, the simultaneous loss of Ikzf1 and Myb, but not the individual mutations, drastically impaired neutrophil production and enlarged the macrophage pool in both zebrafish and mice. Mechanistically, Ikzf1 and Myb formed a complex that targeted irf8 and induced the expression of a long noncoding RNA (lncRNA), irf8-2 , through a regulatory element. LncRNA irf8-2 biased neutrophil commitment by modulating irf8 dosage via Zfp36l1. The deletion of irf8-2 resulted in defective neutrophil development and enhanced macrophage production. However, a partial ratio of neutrophils and macrophages was restored when Ikzf1, Myb, and Irf8 were all compromised. Overall, our study reveals that Ikzf1 and Myb cooperatively bias neutrophil development against Irf8 via the lncRNA irf8 -2 and Zfp36l. This study provides previously uncharacterized insights into the conserved molecular balance between neutrophil and macrophage development during myelopoiesis, with potential implications for understanding and treating myeloid disorders.